Co-optimization of a novel distributed energy system integrated with hybrid energy storage in different nearly zero energy community scenarios. (15th May 2022) - Liu, Zhijian; Li, Ying; Fan, Guangyao; Wu, Di; Guo, Jiacheng; Jin, Guangya; Zhang, Shicong; Yang, Xinyan
Abstract: Many countries have proposed plans on distributed energy systems. However, distributed energy systems still can be improved in system optimization design methods, new-type load, and application scenarios. Therefore, a novel distributed energy system is developed combining solar energy utilization with hybrid energy storage technology, i.e., heat storage and electricity storage. Secondly, with primary energy saving rate, carbon dioxide equivalent emission reduction rate, and annual cost per unit supply area as objectives, an integration optimization method considering equipment configuration and operation strategy is adopted. Then, considering different community types and scales, 12 nearly zero energy community scenarios with electric vehicles as a new-type load are designed. Comparative analysis is conducted on the proposed system, comparing with separated production system and in different scenarios. The results show the scenario with 50% public buildings possesses considerable energy saving (53.1%), environmentally protection (56.4%), and economy (50.1 CNY/m 2 ). The proportion of public buildings mainly influences primary energy saving rate (21.0%), followed by annual cost per unit supply area 17.7 (CNY/m 2 ), finally carbon emission reduction (9.1%). The residential community with 196800 m 2 building scale perform brilliantly. These findings worth popularization and application in the developing nearly zero energy communities. Highlights: A novel distributed energy system is proposed considering hybrid energy storage. The co-optimization method improves the primary energy saving rate by 24.0%. Community with 50% public and 50% residential buildings has optimal energy saving and carbon reduction. Community with 196800 m 2 has marked CO2 reduction (49.8%) and economy (56.5 CNY/m 2 ).